2009
DOI: 10.1677/joe-09-0136
|View full text |Cite
|
Sign up to set email alerts
|

Expression of pregnancy-associated plasma protein A2 during pregnancy in human and mouse

Abstract: Pregnancy-associated plasma protein-A and -A2 (PAPPA and PAPPA2) are proteases that cleave IGF binding proteins (IGFBPs) and thereby increase the bioavailability of growth factors. PAPPA has long been recognized as a marker of fetal genetic disorders and adverse pregnancy outcomes. In contrast, although PAPPA2 is also highly expressed in human placenta, its physiological importance is not clear. To establish whether mice will be a useful model for the study of PAPPA2, we compared the patterns of expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
4
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 44 publications
(61 reference statements)
3
48
4
1
Order By: Relevance
“…It is also the first time that the decreasing expression of PAPPA2 in human placenta along the gestational period was demonstrated. Our observation was different from the report of Wang et al (2009), who found that the PAPPA2 level was increased in maternal circulation along the gestational period (Wang et al, 2009). Thus, it is reasonable to deduce that the maternal circulatory PAPPA2 in the second and third trimester does not originate from the placenta but actually from the maternal body.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…It is also the first time that the decreasing expression of PAPPA2 in human placenta along the gestational period was demonstrated. Our observation was different from the report of Wang et al (2009), who found that the PAPPA2 level was increased in maternal circulation along the gestational period (Wang et al, 2009). Thus, it is reasonable to deduce that the maternal circulatory PAPPA2 in the second and third trimester does not originate from the placenta but actually from the maternal body.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, many factors involved in facilitating trophoblast physiological function have also been revealed (Das et al, 2002). Those gene products include proteases (Wang et al, 2009), growth factors and their receptors (Morrish et al, 2007), cytokines (Das et al, 2002), and proteins involved in maintaining cell structures (Cronier et al, 2002). Normal trophoblast lineage and placentation under the regulation of necessary genes, which undergo intrinsic spatial and temporal expression, is the prerequisite for successful pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…However, the present study appears to be the first to comprehensively compare PAPPA2 immunohistochemistry between PT, PE and term samples and to observe a lack of staining in term samples. Although variable, placental PAPPA2 mRNA levels have also been reported to decline with gestation (Winn et al 2009) and PAPPA2 has been shown to be a cleavage protease for insulin-like growth factor (IGF) binding protein 5 (Wang et al 2009) bioavailability. Thus, the decline in placental PAPPA2 protein observed at term in our immunohistochemical samples is possibly a result of the decreased placental growth occurring during this phase of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy-associated plasma protein A2 (PAPPA2) was up-regulated 2.6-fold (P < 0.001). PAPPA2 protein is elevated in EO PE placenta (24) and maternal serum before PE onset (25) and expressed by first-trimester EVT in women and by invasive trophoblasts in mice (26). However, the functional role of PAPPA2 in EVT invasion is not known.…”
Section: Il11 Impedes Human Evt Invasion Via the Pregnancy-associatedmentioning
confidence: 99%